THE IMPACT OF USING INTERACTIVE MEDIA IN SCIENCE LEARNING IN ELEMENTARY SCHOOLS ON STUDENTS' SCIENTIFIC ATTITUDES AND CONCEPT ACHIEVEMENT - Sepling Paling (International Journal of Teaching and Learning, 2025)
This research aims to examine the impact of using interactive media in natural science (science) learning in elementary schools on students' scientific attitudes and concept achievement. This study was carried out using the Systematic Literature Review (SLR) method by examining various scientific articles, research reports and proceedings from the last ten years. The results of the analysis show that interactive media generally has a positive influence in fostering students' scientific attitudes, such as curiosity, thoroughness, openness to evidence, and cooperation. Apart from that, the use of interactive media has also proven effective in helping students understand abstract science concepts through visualization, simulations and more concrete and meaningful learning experiences. The link between scientific attitude and concept achievement has also been identified in a number of studies, where a good scientific attitude tends to strengthen the process of understanding concepts in depth. However, the effectiveness of interactive media is greatly influenced by various contextual factors, such as the type of media, the level of student development, and the learning strategies implemented by teachers. Therefore, the use of interactive media in science learning needs to be designed appropriately so that it is able to support learning objectives optimally, both in terms of mastery of the material and the formation of students' scientific character from an early age.